Rapid Adaptation of Night Vision - Reeves, Adam; Grayhem, Rebecca; Hwang, Alex D. (Frontiers in Psychology, 2018)
Apart from the well-known loss of color vision and of foveal acuity that characterizes human rod-mediated vision, it has also been thought that night vision is very slow (taking up to 40 minutes) to adapt to changes in light levels. Even cone-mediated, daylight, vision has been thought to take 2 minutes to recover from light adaptation. Here, we show that most, though not all adaptation is rapid, taking less than 0.6 seconds. Thus, monochrome (black-white-grey) images can be presented at mesopic light levels and be visible within a few tenths of a second, even if the overall light level, or level of glare (as with passing headlamps while driving), changes abruptly.